2016
DOI: 10.1634/theoncologist.2016-0049
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Actionability of Comprehensive Genomic Profiling for Management of Rare or Refractory Cancers

Abstract: To study the frequency with which targeted tumor sequencing results will lead to implemented change in care, this study assessed tumors from 100 patients for utility, feasibility, and limitations of genomic sequencing for genomically guided therapy or other clinical purpose in the setting of a multidisciplinary molecular tumor board. Comprehensive profiling led to implementable clinical action in 35% of tumors with genomic alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
52
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 52 publications
11
52
0
3
Order By: Relevance
“…The average number of genetic alterations considered actionable by the board was 1.9 (range, zero to six alterations). Genes recurrently altered across samples were similar to those reported from other series, 911 although the relative frequencies were influenced by the case mix seen by our tumor board (Fig 2). In terms of targetable pathways, the phosphatidylinositol-3 kinase (PI3K) pathway was most frequently altered (63 alterations), followed by the G 1 cell cycle checkpoint (61 alterations) and FGFR pathways (30 alterations).…”
Section: Resultssupporting
confidence: 83%
“…The average number of genetic alterations considered actionable by the board was 1.9 (range, zero to six alterations). Genes recurrently altered across samples were similar to those reported from other series, 911 although the relative frequencies were influenced by the case mix seen by our tumor board (Fig 2). In terms of targetable pathways, the phosphatidylinositol-3 kinase (PI3K) pathway was most frequently altered (63 alterations), followed by the G 1 cell cycle checkpoint (61 alterations) and FGFR pathways (30 alterations).…”
Section: Resultssupporting
confidence: 83%
“…The authors concluded that broad implementation of multiplex hotspot testing is feasible but that only a small portion of the patients with cancer characterized by actionable alterations were actually enrolled onto genotype-matched trials. Other studies on smaller populations have provided support for the ability of comprehensive tumor genomic profiling to direct the point-of-care management of patients with cancer, (10,11) although the percentage of patients subsequently enrolled in genotype-matched clinical trials was similarly low (10).…”
Section: Current Approachesmentioning
confidence: 99%
“…To increase the number of feasible therapeutic options recommended for patients undergoing broad-based genomic sequencing, many center-wide efforts have been initiated (9)(10)(11)(12)(13). These often recommendations to the referring physician in a point-of-care manner, and subsequent follow up of patient outcomes.…”
Section: Current Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this manuscript, we address this problem and introduce LOHGIC (LOH-germline Inference Calculator) to assess germline-versus-somatic status of mutations and predict presence of LOH in tumor-only deep-sequencing data. We evaluate LOHGIC using precision-oncology data collected at Rutgers Cancer Institute of New Jersey 25 , and validate our predictions using available genetic counseling reports.…”
Section: Introductionmentioning
confidence: 99%